The influenza A(H1N1) epidemic in Mexico. Lessons learned - Arzoz-Padrés Jacqueline; Sarti Elsa; Córdova-Villalobos José A; Manuell-Lee Gabriel; Méndez Josefina; Kuri-Morales Pablo (BMC, 2009)
Abstract Several influenza pandemics have taken place throughout history and it was assumed that the pandemic would emerge from a new human virus resulting from the adaptation of an avian virus strain. Mexico, since 2003 had developed a National Preparedness and Response Plan for an Influenza Pandemic focused in risk communication, health promotion, healthcare, epidemiological surveillance, strategic stockpile, research and development. This plan was challenged on April 2009, when a new influenza A(H1N1) strain of swine origen was detected in Mexico. The situation faced, the decisions and actions taken, allowed to control the first epidemic wave in the country. This document describes the critical moments faced and explicitly point out the lessons learned focused on the decided support by the government, the National Pandemic Influenza Plan, the coordination among all the government levels, the presence and solidarity of international organizations with timely and daily information, diagnosis and the positive effect on the population following the preventive hygienic measures recommended by the health authorities. The international community will be able to use the Mexican experience in the interest of global health.